Paul in the Roman world : the conflict at Corinth - Grant, Robert M. (Robert McQueen), 1917-2014 (Louisville, Westminster John Knox Press, 2001)
"Though the apostle Paul wrote letters to many of the churches he founded, none of his extant letters reveal more about him, his missionary activity, and the community of faith he sought to pastor than 1 Corinthians. In 1 Corinthians, Paul tried to influence - even control - the church in the context of a city that had lasting memories of Greek democracy but the present realities of a Roman proconsul. This volume highlights Paul as apostle, missionary, and pastor against the backdrop of the Greco-Roman culture, economics, and politics."--Jacket
Part I Business and Politics -- 1 Journey to Corinth 3 -- 2 Corinth: City and Church 13 -- 3 Religion and Politics 23 -- 4 Some Contemporaries 45 -- Part II Religion and Ritual -- 5 God and the Gods 63 -- 6 Liturgy at Corinth 73 -- 7 Rites in the Second Century
Includes bibliographical references (pages 163-173) and indexes
Includes bibliographical references and index
Keywords: Bible. -- Criticism, interpretation, etc; Church history -- Primitive and early church, ca. 30-600; Corinth (Greece) -- Religious life and customs; Corinth (Greece) -- Social life and customs; Corinth (Greece) -- Social conditions; Corinth (Greece) -- Church history; Korintherbrief (I.)